Acabados para madera en exteriores - Castillo Morales, Ma. Iracema; Erdoiza Sordo, José Javier (Instituto de Ecología, A.C., 1995)
Wood exposed to weathering (rain, wind, sunlight, etc.) can suffer surface damage, which is characterized by a greyish appearance when the exposure is severe. In turn, this can lead to invasion by other agents that can easily cause internal deterioration of the wood. To avoid this problem, it is necessary to protect the wood by applying a mixture of chemical products called finishes or surface coatings. Five kinds of finishes were tested, two of which (varnishes and paints) form a film, while the other three (water repellents, stains, and waterborne preservatives) penetrate the wood. It was demonstrated that stains are more effective at protecting wood from climatic exposure tan the other treatments.